Epstein Barr Virus and Autoimmune Responses in Systemic Lupus Erythematosus - Jog, Neelakshi R.; James, Judith A. (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a complex systemic autoimmune disease. Infections or infectious reactivation are potential triggers for initiation of autoimmunity and for SLE flares. Epstein-Barr virus (EBV) is gamma herpes virus that has been associated with several autoimmune diseases such as SLE, multiple sclerosis, Sjogren’s syndrome, and systemic sclerosis. In this review, we will discuss the recent advances regarding how EBV may contribute to immune dysregulation, and how these mechanisms may relate to SLE disease progression.